Newborn Care Curriculum: Palliative Care for the Newborn - Melanie Anspacher; Angie Burd; John Stroh; Rebekah Conroy (Association of American Medical Colleges, 2017)
Introduction Because pediatric hospitalists have increasing responsibilities in newborn hospitalization, training in perinatal palliative care is beneficial. A 2015 needs assessment revealed 68% of surveyed pediatric hospitalists were interested in more education on this topic. Thus, this learning module was designed to provide a concise, easy-to-use introduction to palliative care for the newborn. Methods This module was developed as part of the computer-based Newborn Care Curriculum to fill a gap in educational resources on perinatal palliative care. The primary tool in this learning module is a PowerPoint slide show with a script in the notes section. Using the presenter mode to view the PowerPoint slide show allows the learner to simultaneously view the slides and read the script for instruction. This module was tested by members of the pediatric hospitalist division at Children's National Health System in Washington, DC. Participants completed a pretest, posttest, and module evaluation. While tested as a self-study tool, the module may also be used in a small-group teaching setting. Results The module was well received during the trial. The average posttest score was 96%, compared to pretest scores of 90%. Learners' comments were overwhelmingly positive, and constructive feedback has been addressed. Discussion This module provides pediatric hospitalists and others who care for newborns with a well-received introduction to perinatal palliative care. The computer-based format of the module adds to its uniqueness and utility.